Technology dissemination on processing coconut coir waste into aesthetic sound absorbers - Ditha Nizaora; Etwin Fibrianie Soeprapto; Puji Astuti Amalia; Rinto Dwi Atmodjo (Universitas Muhammadiyah Magelang, 2021)
This Community Service is aimed at a group of women farmers in Bangun Rejo Village, Tenggarong Seberang District, Kutai Kartanegara Regency. The partners are plantation farmers such as corn, cassava, coconut, banana and rice, some of which are grown seasonally. From the garden, it produces coir waste such as coconut husks. The problem is that the farmers do not have the knowledge and experience in processing the coconut husks waste. This community service is carried out through three stages, namely preliminary design, design development, and final design and prototype. With this community service activity, there will be a transfer of knowledge on coconut coir processing with chopping machine technology so as to produce coco fiber and process it into fiberboard to then produce interior aesthetic element products. The final product is an aesthetic soundproofing absorber. In addition, the team also gave the machine in order to create a diversification of processed coconut husks products so as to create job opportunities and increase the income of the people.